Implications of Job Satisfaction, Organizational Commitment, and Organizational Culture on Organizational Citizenship Behavior in Electrical Professional Organizations in Indonesia - Ahmad Azmy (Politeknik Negeri Bandung, 2021)
This study analyzes the successful implementation of Organizational Citizenship Behavior (OCB) through the roles of job satisfaction, organizational culture, and organizational commitment. The research was conducted at the Indonesian Electrical Contractors Associations using the Partial Least Square (PLS) method. A number of 100 respondents were asked to fill in a questionnaire distributed via a google form. The results explain that both organizational commitment and organizational culture affect positive behavior (OCB) while job satisfaction does not. These three variables have implications for behavior change represented by culture, job satisfaction, and commitment. Thus, it is possible to deduce that the success of organizational citizenship behavior (OCB) is influenced by organizational commitment and culture that shape employee professionalism. As for job satisfaction, it must be improved through a competitive salary system, support among employees, and a conducive work environment.